2019
DOI: 10.31235/osf.io/fmvpe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Norms vs. Global Actors: International Politics, Muslim Identity, and Support for Shariʿa

Abstract: Many scholars argue that local cultures are an impediment to the diffusion of “global” norms. Others point out that local populations domesticate global cultural elements by integrating them into preexisting cultures, generating hybridized systems. In the current study, I argue that local cultures are not necessarily impediments to cultural change and hybridization is only one aspect of cultural domestication. Instead, I find that individuals attribute global norms to local cultural objects as a means for disa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Items were summed to create scores on Attitudes toward Women's Rights and Roles (Kostenko et al, 2016). Similar to past research examining women's rights indices in developing countries (Ciftci, 2012;Gorman, 2019;Kostenko et al, 2016;Kurzman et al, 2019), we found a modest coefficient alpha of 0.62.…”
Section: Methodssupporting
confidence: 71%
“…Items were summed to create scores on Attitudes toward Women's Rights and Roles (Kostenko et al, 2016). Similar to past research examining women's rights indices in developing countries (Ciftci, 2012;Gorman, 2019;Kostenko et al, 2016;Kurzman et al, 2019), we found a modest coefficient alpha of 0.62.…”
Section: Methodssupporting
confidence: 71%
“…The tension between these judgments is the focus of considerable research. Zakia Salime (2011) and Brandon Gorman (2019) , for example, have explored the competition and interaction between women’s movements in North Africa that promote European-inspired ideals and movements that adopt Islamic discourses of gender equality. Rajaram and Zararia (2009) investigate three women’s rights organizations in one city in India—each group drawing on leftist, feminist, or local approaches to rights—that even use different words for rights.…”
Section: Two Centuries Of Debatementioning
confidence: 99%
“…Tounissiet also opposed it. They believe that most Tunisians favor the existing law as observant Muslims and do not wish to divorce it from Islam, which polling data supports (Gorman 2019, Quillen 2018.…”
Section: Third Phase Of the Democratic Transition (2018)mentioning
confidence: 92%